Analysis of the impact of Tilapia Aquaculture Village Development (Oreochromis niloticus) on the welfare of fish farmers in Ponoragan Village, Loa Kulu District, Kutai Kartanegara Regency - Yolanda, Margaretha; Syafril, Muhammad; Sulistianto, Erwan (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2025)
This study aims to analyze the impact before and after the implementation of Ministerial Regulation of Marine Affairs and Fisheries (Permen-KP) No. 16 of 2022 on the Tilapia Aquaculture Village in Ponoragan Village on household income, employment absorption, and to identify the main challenges faced by fish farmers. The sampling method used was purposive sampling, with a total of 30 tilapia farmers as respondents and two key informants. The data were analyzed using income analysis, average income difference analysis with a T-test, and labor absorption analysis. The study results show that the average income of tilapia farmers before the implementation of the aquaculture village policy was IDR 120,569,272 per month, increasing to IDR 606,954,928 per month after implementation. This indicates a rise in the average income of fish farmers by IDR 486,385,656 following the policy's implementation. The implementation of the aquaculture village policy also had an impact on labor absorption, both from within and outside the family. Before the policy was implemented, the percentage of labor from within the family was 0.01228 percent, increasing to 0.01283 percent after implementation. Meanwhile, the percentage of labor absorption from outside the family increased from 0.01283 percent to 0.01897 percent. This increase reflects the additional workforce employed, both from within and outside the family, in response to increased production, income, and the farmers' commitment to involving the surrounding community. The main challenges faced by tilapia farmers include extreme weather conditions that often cause harvest failures, river water intrusion into ponds, which increases water volume and leads to fish escaping, and the use of pesticides by farmers to control fish pests and predators. These findings illustrate that the aquaculture village policy has great potential to improve farmers' welfare, but it must be accompanied by mitigation efforts to address existing challenges.